2014
DOI: 10.2174/1874213001407010037
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Fire and Commercial Thinning on Future Habitat of the Northern Spotted Owl

Abstract: Abstract:The Northern Spotted Owl (Strix occidentalis caurina) is an emblematic, threatened raptor associated with dense, late-successional forests in the Pacific Northwest, USA. Concerns over high-severity fire and reduced timber harvesting have led to programs to commercially thin forests, and this may occur within habitat designated as "critical" for spotted owls. However, thinning is only allowed under the U.S. Government spotted owl guidelines if the long-term benefits clearly outweigh adverse impacts. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 49 publications
0
21
0
Order By: Relevance
“…This assumption may overestimate the loss of habitat to fire. Odion et al (2014) also found that thinning treatments in fire-prone landscapes reduced owl habitat more than did wildfire.…”
Section: Discussionmentioning
confidence: 83%
“…This assumption may overestimate the loss of habitat to fire. Odion et al (2014) also found that thinning treatments in fire-prone landscapes reduced owl habitat more than did wildfire.…”
Section: Discussionmentioning
confidence: 83%
“…Currently, a deficit in high-severity fire exists in most of western North America compared to historical levels [49,54]. Recruitment of older forests in dry ecoprovinces of the region is projected to outpace fire losses for the next several decades [55].…”
Section: Northern Spotted Owl Decline Slowed But Not Reversedmentioning
confidence: 99%
“…However, forest thinning may lead to cumulative losses in owl habitat that exceed those from severe fires. Using state transition models that accounted for recruitment of owl habitat over time vs. presumed habitat losses from severe fires, Odion et al [55] concluded that thinning of suitable owl habitat at intensities (22% to 45% of dry forest provinces) recommended by USFWS [40] would reduce LSOG three to seven times more than loss attributed to high-severity fires. Projected thinning losses were consistent with empirically based studies of habitat loss from thinning that reduced overstory canopy below minimum thresholds for owl prey species [56].…”
Section: Northern Spotted Owl Decline Slowed But Not Reversedmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, NSO habitat and old-growth forests were likely maintained by mixed-severity fires. Efforts to reduce fuels and to prevent these fires in all areas will likely reduce future NSO habitat (see also Odion et al 2014). To maintain NSO habitat likely first requires restoration of historical fuels, which included abundant shrubs, small trees, and dense forests (Baker 2012).…”
Section: Old-growth Forest and Mixed-severity Firesmentioning
confidence: 99%